Empowering Traditional Education Institution Through the Implementation of Potable Water Provision System - Rini Nur Hasanah; Ainul Hayat; Moh. Farid Rahman; Zainul Abidin; Hadi Suyono (Widyagama University of Malang, 2021)
The activity reported in this journal was aimed to empower the traditional education institutions commonly found and not formally financed by government of Indonesia. Empowering was carried out through the implementation of an action plan to ensure the potable water provision. Clean as well as potable water is indispensable for daily life and activities of students and teachers, especially those who were living and boarding in the school complex. The action was also potential to improve the financial independence of organization and to develop the entrepreneurship skills of students. The obtained tangible results of the action were in the form of production facility with ready-to-drink water quality of less than 10 ppm (parts per million) of total dissolved solids.